Viability Test of Mycobacterium Tuberculosis Bacteria Stored in Various Cryopreservation Periods - Annisa, Jessi; Susilawati, Neng Rina; Asarina, Shinta; Jihadah, Muti'ah Nurul; Chaidir, Lidya (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: The specimen storage room serves as bioarchive for prospective research purposes. Cryopreservation or preservation at very low temperatures has been used to preserve research isolates for decades. A quality assessment must be conducted to ensure the isolates conditions. This study aimed to assess the quality of isolates by testing the level of viability and contamination from different cryopreservation periods.Methods: This was an experimental study with a total sample of 92 Mycobacterium tuberculosis (Mtb) isolates which were sampled randomly using cryopreservation, aged 8–10 years (in Tryptic Soy Broth media, TSB/) and aged 3–5 years (in Middlebrook 7H9) which was re-cultured in Ogawa Medium at the Tuberculosis Laboratory, Universitas Padjadjaran in May–November 2019. After observing confluent growths, the pure isolate was stained using the Ziehl-Neelsen (ZN) method to confirm the presence of Mtb growth or contamination. A Simple ratio was used to count the recovery rate as a viability parameter and contamination rate of each batch.Results: Test results showed a recovery rate of 66.67–100% of positive cultures stored despite they had been cryopreserved for 10 years. There was no significant difference in the percentage of positive cultures between preservation period groups.Conclusion: Mtb isolates can survive and remain viable after being stored for up to 10 years at -80 ° C in cryopreservation media.